Aposymbiotic interactions of three ambrosia beetle fungi with avocado trees. (June 2019) - Freeman, Stanley; Miller, Golan; Protasov, Alex; Maymon, Marcel; Elazar, Meirav; David-Schwartz, Rakefet; Zhou, Jing; Mendel, Zvi
Abstract: Interactions between the fungal symbionts of the polyphagous shot hole borer (PSHB) Euwallacea nr. fornicatus and avocado host trees of cultivars 'Hass' and 'Ettinger' were studied, with emphasis on the three symbiotic fungi of the beetle. Fusarium euwallaceae did not spread far from the beetle galleries and remained viable in live xylem for 25 months; Graphium euwallaceae and Paracremonium pembeum disappeared from the live tissue 2 months after inoculation, but remained viable in dead xylem. The role of F. euwallaceae as a pathogen that contributes to typical wilting symptoms of PSHB-colonized avocado branches was assessed. The enhanced resistance of 'Ettinger' than of 'Hass', as manifested in its fewer beetle attacks was not reflected in the interaction of these cultivars with the symbiotic fungi. The specific pseudo-pathogenic interaction of F. euwallaceae with the xylem may be the key to understanding the different susceptibility between attacked hosts. Highlights: F. euwallaceae did not spread further than 10 cm away from the beetle galleries. FE remained viable in live tissue at least two years after inoculation. G. euwallaceae and P. pembeum were not recovered a few months after inoculation. GE and PP persist in dying or dead xylem and enable long-distance travel of the beetle. FE causes wilting of branches only in association with beetle colonized xylem.